Mechanical correction in kinesiology and mulligan taping: A comparative study on scapular dyskinesis in computer users. - Khaki, Shahab; Ravanbod, Roya; Ashtiani, Mohammed N. (Journal of Back & Musculoskeletal Rehabilitation, 2025)
Background: Poor scapular resting position and abnormal motion with the lack of proper muscle performance contribute to the development of shoulder dysfunction and pain. Various taping methods was proven to stabilize the scapula in a retracted position and facilitate proper scapular motion. Objectives: To compare the effects of mechanical correction of kinesiology tape (KT) and mulligan tape (MuT) methods on electromyographic activity (EMG) and kinematics of scapulothoracic (ST) and kinetics of glenohumeral (GH) joints in computer users affected with scapular dyskinesis (SD). Methods: This study is a single-blinded randomized placebo-controlled clinical trial study with convenience sampling. Thirty-six male computer users with SD were randomized in three groups of KT, MuT, and placebo tape (PT). A two-session evaluation, in each session two times, with a 72-h interval was done. The outcome measures of the EMG were peak root mean square (PRMS) and RMS activity of upper trapezius (UT), middle trapezius (MT), lower trapezius (LT), deltoid (Del), and serratus anterior (SA) muscles during typing and 120° of scaption tasks. Anterior tipping, upward rotation, and internal rotation of the scapula were also recorded using a motion capture system and processed using custom code written in Matlab (R2015b; Mathworks, Inc., Natick, MA). Results: In MuT, PRMS and RMS of UT and MT; PRMS of SA in 120° scaption; and RMS of MT in typing position increased significantly (p < 0.05). In KT, SA RMS in 120° scaption increased and internal and upward rotation of scapula in typing position decreased significantly (p < 0.05). Conclusion: Mulligan tape showed a better effect on increasing EMG activity of the muscles which have a controlling role in SD correction and KT had a better impact on decreasing scapula internal rotation which is typically impaired in SD.